Impact of development and application of advanced technology on labor productivity and energy management efficiency in Vietnam - Thi Thu Huong Tran; Bich Ngoc Nguyen (Center of Biomass & Renewable Energy (CBIORE), 2026)
Digital technology enhances labor productivity by automating repetitive tasks and improving data-driven decision-making, while simultaneously increasing energy management efficiency through smart monitoring and optimization systems. Therefore, this study examines the impact of advanced digital technology (proxied by internet penetration) on labor productivity and energy management efficiency in Vietnam using ARDL analysis of annual data from 1990 to 2024. The model includes internet penetration, GDP per person employed (labor productivity), renewable energy consumption, and GDP growth. ADF and PP tests confirm a mixed order of integration, I (0)/I (1), justifying the use of ARDL bounds testing. Descriptive analysis indicates rapid digitalization, with internet penetration increasing from 0% to 84.15%, alongside steady productivity growth, while renewable energy consumption exhibits a strong negative correlation with the time trend (r = -0.9855), suggesting a declining pattern. ARDL results reveal very high persistence in labor productivity (lagged coefficient = 0.9929, p < 0.001). GDP growth exerts significant short-run effects, whereas internet penetration shows a delayed impact, with an insignificant contemporaneous coefficient but a positive lagged effect. Long-run estimates suggest continued productivity momentum and positive contributions from digitalization and macroeconomic growth. However, the error correction term is positive and statistically insignificant (0.1681, p = 0.597), indicating the absence of a stable long-run equilibrium relationship. Diagnostic tests confirm residual normality and homoscedasticity, while the Durbin–Watson statistic (1.5403) suggests mild positive autocorrelation. Overall, the findings highlight delayed productivity gains from digital infrastructure, emphasizing the need for complementary institutional and structural adjustments.